Generation of three human induced pluripotent stem cell lines from retinitis pigmentosa 25 patient and two carriers but asymptomatic daughters - Helena Isla-Magrané; Maddalen Zufiaurre-Seijo; Miguel Ángel Zapata; Josep García-Arumí; Anna Duarri (Stem Cell Research)
Retinitis Pigmentosa type 25 (RP25) is a form of inherited retinal dystrophy characterized by a progressive loss of rod photoreceptors, subsequent degeneration of cone photoreceptors, and eventually, the retinal pigment epithelium. Caused by mutations in the EYS gene, it is believed to be critical for the structural and functional integrity of the retina. Using a non-integrative RNA reprogramming method, we have generated human induced pluripotent stem cell (hiPSC) lines from RP25 patient and from carriers but asymptomatic daughters. These three hiPSC lines maintain a normal karyotype, exhibit pluripotency gene expression, and can differentiate into the three germ layers.